Real option value approach to firm valuation under price uncertainty - TABORA, CARLOS SANTIAGO (Archīum Ateneo, 2018)
This study uses the Andres-Alonso et al (2006) model, and Cox, Ross, and Rubinstein (1979) binomial option pricing model to determine the real option value (ROV) and expected net present value (ENPV) of a firm under price uncertainty, to verify the sign of the difference between the ROV and ENPV (ROV-ENPV difference), and to estimate the price uncertainty effect of the ROV-ENPV difference. A panel dataset of 120 observations of the Philippine Stock Exchange indexs blue-chip firms ROV-ENPV difference are regressed on the firms revenue, asset beta, asset size, debt level, price volatility, and sector using the instrument variable-feasible generalized least squares regression approach of Hausman and Taylor (1981). Results show that the asset beta and price volatility values define the sign of the ROV-ENPV difference. The ROV will be lower than the ENPV, if the asset beta effect is greater than the price volatility effect. Otherwise, the ROV will be higher than ENPV. The ROV-ENPV difference is predicted to increase by about Php516 million for every 0.01 unit of price volatility under base discount rate condition holding other variables constant. Results of the sensitivity analysis on the discount rate confirm that the asset beta and price volatility effects on the ROV-ENPV difference hold, even if a premium or discount is added to the discount rate to account for the price uncertainty.